DIVERSIFIKASI AGROBISNIS DAN WAKAF PRODUKTIF SEBAGAI STRATEGI PEMBIAYAAN BERKELANJUTAN LEMBAGA PENDIDIKAN ISLAM - Hidayani, Erda Farid; Harsono; Suyatmini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to construct a substantive theory of agribusiness and productive waqf diversification as a sustainable financing strategy for Islamic educational institutions. The research is grounded in the fact that many Islamic schools and pesantren still depend heavily on a single funding source, such as student tuition, which creates financial vulnerability and limits institutional innovation. Although agribusiness and productive waqf have been discussed as alternative funding schemes, few studies have explained in depth how Islamic values shape the economic and managerial practices that sustain educational financing. Using a qualitative Grounded Theory approach, this study explores the social processes and meanings constructed by educational stakeholders through in-depth interviews, participatory observation, and document analysis at a waqf-based school operating a productive agribusiness unit. Data were analyzed through open, axial, and selective coding to identify core categories and develop a conceptual model of value-based sustainable financing. The findings reveal that Islamic values such as amanah (trust), barakah (divine blessing), and productive waqf management serve as the moral foundation guiding the institution’s financial behavior. Agribusiness and waqf diversification not only strengthen financial resilience but also function as entrepreneurial learning media and instruments of spiritual character formation. The study develops the “Value-Based Agribusiness and Productive Waqf Diversification Model”, which integrates moral, social, and managerial dimensions as a theoretical basis for sustainable Islamic educational financing. Keywords: Agribusiness diversification, productive waqf, sustainable financing, Islamic education, Grounded Theory